Impact of Financialization on Income Inequality in Aspect of Welfare - Diliuvienė, Laura; Tamašauskienė, Zita (Socialiniai tyrimai, 2021)
Recently income inequality has been growing in many countries, and it is one of the biggest economic and social problems. The International Monetary Fund, the Organization for Economic Co-operation and Development (OECD), and other organizations stress the importance of this issue. According to Atkinson, Brandolini (2009), changes in income inequality show whether a particular society becomes more egalitarian over time or not, in which socio-economic direction it progresses.Even countries with similar economic structures differ in the level of income inequality and, according to Stiglitz (2015), differences in income inequality are related to policy decisions. The decisions of countries may depend on the prevailing view if markets are efficient or inefficient. In the first case, countries tend to rely more on neoliberal economic doctrine, and in the second, on the welfare state, where the role of government is more active (Stiglitz, 2017). However, it is observed that the growing income inequality is related to the growing role of the financial market, i.e. the phenomenon of financialization, which weakens the role of government. Thus, assessing the impact of financialization on income inequality is an actual topic of scientific debate.The results of studies, assessing the impact of financialization on income inequality, are mixed. Some financialization dimensions, such as financial liberalization, banking / financial crises increase income inequality, but microfinance intensity reduces income inequality. The contradictory results can be explained by the fact that research samples differ, various indicators reflecting the financialization are used, different independent variables are included in the regression equations.Studies have also been conducted in groups of countries that belong to different welfare state regimes (Josifidis, Mitrović, Supić, Glavaški, 2016; Dafermos, Papatheodorou, 2013). These studies emphasize that the level of income inequality is related to the efficiency of the social security system, i.e. income inequality is lower in Social–democratic welfare state regime (inherent universal social services and benefits) and Conservative–corporatist welfare state regime (social security model related to employment status) groups of countries than in the Mediterranean welfare state regime (characterized by the fragmentation of the social security model) and Liberal welfare state regime (inherent the specificity of the social security model, there is no universality) groups of countries. However, there is a lack of research that assesses the impact of financialization on income inequality in different welfare state regime groups of countries. The research problem: what is the impact of financialization on income inequality, is this impact the same in different EU welfare state regime groups? The object of the research - the impact of financialization on income inequality. The aim of the research is to assess the impact of financialization on income inequality in EU country groups.Research methods: analysis of scientific literature, grouping, generalization, regression analysis of panel data.When assessing the impact of financialization on income inequality in different welfare regimes EU country groups during the period 1998-2017, the least-squares regression analysis method of the panel data was used. The conducted research confirms the hypothesis and clearly shows that financialization, measured both by financial development index and domestic credit to the private sector, increases income inequality in all groups of countries. Thus, it shows that the role of the financial market is growing and financialization processes are contributing to the growth of income inequality in all groups of welfare regime countries and may reduce the role of government. These results are in line with Stiglitz, 2012; Razgūnė, 2017; Dünhaupt, 2014; Golebiowski, Szczepankowski, Wisniewska, 2016; Palley, 2008) who analyzed the relationship between financialization and growing income inequality. However, the study of Dabla-Norris et al. (2015), by contrast, find that the ratio of domestic credit to GDP in developed countries reduces income inequality.
Keywords: income inequality; financialization; welfare regimes